Does multicultural Indonesia include its ethnic Chinese? - Anggraeni, Dewi (UI Scholars Hub, 2011)
Multiculturalism in Indonesia is predominantly concerned with various regional cultures in the country, which continue to exist, and in some cases, to develop and progress. These cultures meet and interact in the context of a unitary national, Indonesian culture. There are however people who or whose ancestors originate from outside Indonesia, the major ones being Chinese and Arabs. They brought with them the cultures and mores of their lands of origin and to varying degrees integrated them into those of the places they adopted as homes. This article discusses how the Chinese who opted for Indonesian citizenship and nationality, fared and fare in Indonesia's multicultural society, what problems slowed them in their path, and what lies behind these problems.